Design of Business Process Improvement Survey of Business Activities With Business Process Improvement Approach - Nur Azizah, Amalia; Lalu, Heriyono; Salma, Sheila Amalia (Journal Knowledge Industrial Engineering (JKIE), 2021)
Bank Indonesia Representative Office West Java is one of the companies that makes data and information a very important asset. One of the main ways to obtain data or information is by conducting a survey, namely the Survei Kegiatan Dunia Usaha (SKDU). In actual conditions, the SKDU process has not been implemented properly, causing a low level of validity and delays in processing time. so this study aims to design a proposed business process to increase the level of validity and reduce processing time. This research method uses Business Process Improvement which is carried out in 4 stages, namely identifying business needs and processes, then modeling and analyzing to find out the cause of the problem, and redesigning the process. The result of this research is the business process improvement by applying value added and automation techniques results in a reduced number of activities in business processes, reduced process actors.